(untitled) (Research, Society and Development, 2023)
This study aimed to characterize the properties of wood from Pinus caribaea var. hondurensis and Pinus caribaea var bahamensis, in 7-year-old individuals, in the municipality of Batatais, State of São Paulo, Brazil. For this, twelve trees of each species/variety were felled, and a 1 m long log was removed from the base of each tree. Samples were taken from the obtained logs to evaluate the physical-mechanical properties of the wood. It was verified that the woods of Pinus caribaea var. hondurensis and Pinus caribaea var. bahamensis do not differ significantly from each other for: Apparent density, basic density, compression parallel to the grain, shear parallel to grain, modulus of elasticity, volumetric shrinkage, anisotropy coefficient, radial shrinkage, and tangential shrinkage. The wood of the species/variety Pinus caribaea var. bahamensis showed a significantly higher modulus of rupture than the variety Pinus caribaea var. hondurensis. Regarding the use of wood from these species/variety, at a younger age, both showed potential use for different purposes. Since this initial assessment can be used as an indication of pre-selection of wood for the various segments of the timber industry, mainly for uses that do not have many restrictions in structural applications and dimensional variation.